2010
DOI: 10.1002/arch.20388
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of proteolytic activities in seven species of synanthropic acaridid mites

Abstract: Microplate assays with 96 wells were optimized to screen proteolytic activities in mite homogenates. Whole-mite extracts of Acarus siro, Aleuroglyphus ovatus, Tyrophagus putrescentiae, Tyroborus lini, Carpoglyphus lactis, Lepidoglyphus destructor, and Dermatophagoides farinae exhibited non-specific proteolytic activity in buffers from pH 2 to 12, and three peaks of highest activity at pH 3, 5-6, and 10 were distinguished. The reducing agent Tris(2-carboxyethyl)phosphine hydrochloride decreased general proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Overall, many other species of sarcoptiform mites, including many free‐living Astigmata, are functionally defined as fungivore–microbivore–detritivores (e.g., Pyroglyphidae and most oribatid mites, Walter & Proctor 2013a,b), and our results also support this classification for feather mites. In fact, our results are in large agreement with previous studies on microbes found in other mite species (Chaisiri, McGarry, Morand, & Makepeace, ; Hubert et al., ), where strong evidence has been found for the utilization of bacteria as a food source in free‐living astigmatan species (Erban & Hubert, , ; Hubert, Nesvorna, Kopecký, Ságová‐Marečková, & Poltronieri, ; Hubert et al., ). In these studies, microbiomes composed of highly diverse taxa in low abundance have been interpreted as evidence for microbivory.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, many other species of sarcoptiform mites, including many free‐living Astigmata, are functionally defined as fungivore–microbivore–detritivores (e.g., Pyroglyphidae and most oribatid mites, Walter & Proctor 2013a,b), and our results also support this classification for feather mites. In fact, our results are in large agreement with previous studies on microbes found in other mite species (Chaisiri, McGarry, Morand, & Makepeace, ; Hubert et al., ), where strong evidence has been found for the utilization of bacteria as a food source in free‐living astigmatan species (Erban & Hubert, , ; Hubert, Nesvorna, Kopecký, Ságová‐Marečková, & Poltronieri, ; Hubert et al., ). In these studies, microbiomes composed of highly diverse taxa in low abundance have been interpreted as evidence for microbivory.…”
Section: Discussionsupporting
confidence: 92%
“…The microbial diets of mites can supply proteins, starch, nitrogen and lipids (Erban and Hubert ). The gut of C. lactis has enzymes (lysozyme and proteases) with hydrolytic activity against bacterial and yeast cell walls (Childs and Bowman ; Erban and Hubert , ,b, ). The gut environment is suitable for enzymatic activities because the pH of mesodeum was in the range 4·5–5 in ventriculus and caeca, 5–6 in colon and 5·5–7 in postcolon (Erban and Hubert ).…”
Section: Discussionmentioning
confidence: 99%
“…Scale: 100 mm. mesodeum of L. destructor was studied using whole mite extracts and both unspecific and specific substrates (Bowman, 1981;Erban and Hubert, 2010a). For better understanding of protein digestion in mites, it is necessary to demonstrate the localization of the activities in the gut and/or to determine enzymatic activity in feces.…”
Section: Discussionmentioning
confidence: 99%